The spiritual language of art : medieval Christian themes in writings on art of the Italian Renaissance - Stowell, Steven, 1979- (Studies in medieval and Reformation traditions, 2014)
Analyzing the literature on art from the Italian Renaissance, The Spiritual Language of Art explores the complex relationship between visual art and spirituality by revealing that terms, concepts and metaphors derived from spiritual literature were consistently used to discuss art.